2015
DOI: 10.4317/medoral.20030
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive study of the patients treated at the clinic integrated dentistry for patients with special needs at Complutense University of Madrid (2003-2012)

Abstract: Objectives: To study clinical and epidemiological characteristics of the patients treated at the clinic “Integrated Dentistry for Patients with Special Needs (Special Care Dentistry)” at Complutense University of Madrid (UCM), as well as to know the dental treatments performed in these patients and the modifications from the usual treatment protocol. The information obtained from the results could also be applied in order to assess the needs of dental students education about this type of patients. Study Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
2
18
1
1
Order By: Relevance
“…It was found that, in relation to gender, the percentage of female PSNs was higher in relation to males, disagreeing with other studies published in scientific literature performed in dental specialties centers, university dental clinics and dental outpatient clinics of hospitals and pediatric rehabilitation centers of Feira de Santana (Bahia) [4], São Paulo (São Paulo) [5], Porto Alegre (Rio Grande do Sul) [9], Niterói (Rio de Janeiro) [10], Natal (Rio Grande do Norte) [7,12] and Madrid (Spain) [13]. The greater demand of women for dental treatment seems to be related to their greater concern with general and oral health [3,14,15].…”
Section: Resultscontrasting
confidence: 74%
“…It was found that, in relation to gender, the percentage of female PSNs was higher in relation to males, disagreeing with other studies published in scientific literature performed in dental specialties centers, university dental clinics and dental outpatient clinics of hospitals and pediatric rehabilitation centers of Feira de Santana (Bahia) [4], São Paulo (São Paulo) [5], Porto Alegre (Rio Grande do Sul) [9], Niterói (Rio de Janeiro) [10], Natal (Rio Grande do Norte) [7,12] and Madrid (Spain) [13]. The greater demand of women for dental treatment seems to be related to their greater concern with general and oral health [3,14,15].…”
Section: Resultscontrasting
confidence: 74%
“…Dental patients with systemic diseases that require an accurate knowledge of pathogenesis have been increasing [8,9]. In order to diagnose and treat these patients correctly, dentists need to be familiar with cardiovascular, respiratory, immune, endocrine, metabolic diseases, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding future trials, it would be interesting to compare the use of the DB and other digital tools as a substitute for toothbrushing. Indeed, it would be noteworthy to evaluate the effects of these tools, initially in periodontally‐healthy patients, and then in patients with diverse systemic chronic diseases, elderly patients with several pathologies, and patients with physical or mental disabilities, who have difficulties in managing motor skills and find home dental care complicated . Some of these individuals are not self‐sufficient with oral hygiene procedures and often do not collaborate with caregivers, which create barriers in providing consistent and thorough oral hygiene instructions to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these individuals are not self‐sufficient with oral hygiene procedures and often do not collaborate with caregivers, which create barriers in providing consistent and thorough oral hygiene instructions to these patients. Caregivers often resort to the use of cotton swabs and gauzes for cleaning patients’ teeth and gums …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation